Analysing technical efficiency and the profitability of banks in Vietnam - Phi, Kiet (2014)
This study examines the technical efficiency as well as determinants of bank profitability of 43 banks in Vietnam in the period of 2004-2013. First, bank technical efficiency is estimated under the stochastic frontier analysis (SFA) method applying translog input distance function where environment influence is accommodated by one-step procedure using maximum likelihood estimation. Second, three different groups of determinants, namely bank-specific (including technical efficiency), industry-specific and macroeconomic factors, affecting the Vietnamese banking system profitability will be examined by using system GMM. Overall, in terms of efficiency, the average technical efficiency level is around 73.8% and the period also witnessed a decreasing trend with the gap of efficiency between banks widening throughout the period. With respect to bank performance, empirical results provide evidence that the profitability of Vietnamese banks is shaped by bank-specific factors (including technical efficiency) and macroeconomic control variables. Industry structure does not seem to significantly affect profitability.